Survival Benefit of Traditional Chinese Herbal Medicine (A Herbal Formula for Invigorating Spleen) in Gastric Cancer Patients with Peritoneal Metastasis. (2nd March 2014) - Zhao, Lu; Zhao, Ai-Guang; Zhao, Gang; Xu, Yan; Zhu, Xiao-Hong; Cao, Ni-Da; Zheng, Jian; Yang, Jin-Kun; Xu, Jian-Hua
Abstract : Objective. We evaluated the efficiency of traditional Chinese herbal medicine (a compound herbal formula for invigorating spleen) as a complementary and alternative therapy for gastric cancer patients with peritoneal metastasis. Methods. Between 2001 and 2012, 93 gastric cancer patients with peritoneal metastasis were enrolled in this study. The effect of traditional Chinese herbal medicine on their long-term outcome was investigated. Kaplan-Meier method was used to assess the difference in survival time, and Cox proportional hazards regression analysis was performed to identify independent prognostic factors. Result. First-line palliative chemotherapy plus traditional Chinese herbal medicine was performed in 47 patients and the other 46 patients received chemotherapy alone. The overall survival was different between patients with and without traditional Chinese herbal medicine (12.0 versus 10.5 months; P = 0 . 046 ). According to the Cox proportional hazard model, first-line chemotherapy cycle (hazards ratio [HR] = 0.527; 95% CI = 0.323~0.860) and TCHM (hazards ratio [HR] = 0.644; 95% CI = 0.481~0.992) were selected as independent prognostic factors for survival. Conclusion. The results suggest that traditional Chinese herbal medicine could improve the prognosis of the gastric cancer patients with peritoneal metastasis.